2022
DOI: 10.12998/wjcc.v10.i4.1140
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Gastrointestinal manifestations, liver injury and recommendations

Abstract: Coronavirus disease 2019 (COVID-19) has caused a pandemic that affected all countries with nearly 270 million patients and 5 million deaths, as of as of December, 2021. The severe acute respiratory syndrome coronavirus 2 virus targets the receptor, angiotensin-converting enzyme 2, which is frequently found in human intestinal epithelial cells, bile duct epithelial cells, and liver cells, and all gastrointestinal system organs are affected by COVID-19 infection. The aim of this study is to review the gastrointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 113 publications
(263 reference statements)
0
25
0
6
Order By: Relevance
“…In addition, the increase in bilirubin levels at time of hospital admission is significantly related to hospital mortality; however, also considering the minor association, further research is required to validate the data shown. Considering the need for tools and prognostic examinations that can help to predict the clinical progression of disease in COVID-19 patients, our study, with others recently published [8][9][10][11][12][13][14][15][16][17][18][19], could be a useful guide, using liver damage and liver function tests to highlight patients at risk of COVID-19 progression or to predict the severity of disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the increase in bilirubin levels at time of hospital admission is significantly related to hospital mortality; however, also considering the minor association, further research is required to validate the data shown. Considering the need for tools and prognostic examinations that can help to predict the clinical progression of disease in COVID-19 patients, our study, with others recently published [8][9][10][11][12][13][14][15][16][17][18][19], could be a useful guide, using liver damage and liver function tests to highlight patients at risk of COVID-19 progression or to predict the severity of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Liver damage is likely multifactorial: it may be due not only to direct viral damage, but also due to a systemic cytokine storm, pro-thrombotic state, drug use and abuse during COVID-19, and hypoxic injury [8]. Finally, several studies have investigated the role of liver enzymes on disease progression and mortality [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], showing a relation between the elevation of liver enzymes, considered as a manifestation of liver damage, and the severity of COVID-19 disease. In addition, the impact that the SARS-CoV-2 pandemic has determined on patients with liver disease has been considerable for both outpatient and inpatient management [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A tocilizumab alkalmazása mellett a leggyakrabban átmeneti szérum-GPT-aktivitás-emelkedés fordul elő a betegek pár százalékában [17]. További következménye lehet a HBV-reaktiváció, mely a májsejtek pusztulása révén idézhet elő magas májenzim-aktivitást [18]. A baricitinib kis molekula súlyú JAK-inhibitor.…”
Section: Gyógyszer Okozta Májkárosodásunclassified
“…A májenzim-emelkedés >10%-ban előforduló mellékhatás a gyógyszer leirata szerint [19]. Baricitinib szedése mellett is tisztázni kell a beteg HBV-statusát az esetleges reaktiváció elkerülése, illetve obszervációja és felismerése céljából [18]. A favipiravir RNS-dependens RNS-polimeráz-gátló antivirális készítmény [20].…”
Section: Gyógyszer Okozta Májkárosodásunclassified
“…Среди множества гастроэнтерологических проявлений у пациентов с COVID-19 наиболее часто регистрируется диарея [12]. В некоторых выборках частота данного симптома достигала 49,5% [12,13]. В крупнейшей российской когорте пациентов с COVID-19 (n=3764) распространенность диареи у госпитализированных больных составила 15,04% (95% ДИ 13,90-16,19) [10].…”
Section: Introductionunclassified